2011
DOI: 10.1128/aac.00157-11
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir (S/GSK1349572) Exhibits Significantly Slower Dissociation than Raltegravir and Elvitegravir from Wild-Type and Integrase Inhibitor-Resistant HIV-1 Integrase-DNA Complexes

Abstract: The integrase inhibitor (INI) dolutegravir (DTG; S/GSK1349572

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
195
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(207 citation statements)
references
References 38 publications
(47 reference statements)
11
195
0
1
Order By: Relevance
“…Instead, the substitutions appear to subtly affect local active site geometry, such that binding of the drug to mutant enzymes requires significant energetically unfavorable rearrangement of the IN CCD (68). Consistent with this interpretation, resistance changes correlate with significant increases in drug dissociation rates from these enzymes (71). The PIC harbors a unique enzymatic antiviral target: formed through IN processing of the LTR ends in the cytoplasm, the functional CDC must persist for sufficient time to accommodate PIC nuclear import, chromatin targeting, and IN strand transfer activity (Fig.…”
Section: In Strand Transfer Inhibitorssupporting
confidence: 59%
See 1 more Smart Citation
“…Instead, the substitutions appear to subtly affect local active site geometry, such that binding of the drug to mutant enzymes requires significant energetically unfavorable rearrangement of the IN CCD (68). Consistent with this interpretation, resistance changes correlate with significant increases in drug dissociation rates from these enzymes (71). The PIC harbors a unique enzymatic antiviral target: formed through IN processing of the LTR ends in the cytoplasm, the functional CDC must persist for sufficient time to accommodate PIC nuclear import, chromatin targeting, and IN strand transfer activity (Fig.…”
Section: In Strand Transfer Inhibitorssupporting
confidence: 59%
“…Co-crystallization with the PFV CDC revealed an extended linker region between the metal-binding heteroatoms and the halobenzyl arm that allowed the drug to intimately contact the viral LTR end and IN ␤4-␣2 loop region (Fig. 3B) (69), likely contributing to the slower dissociation of DTG versus RAL from HIV-1 IN-LTR complexes in vitro (71). The relative difficulty in selecting for DTG-resistant viruses ex vivo (47) suggests that the generation of resistance in vivo might occur less frequently than what has been seen with RAL.…”
Section: In Strand Transfer Inhibitorsmentioning
confidence: 99%
“…Interestingly, no additional compensatory mutations have been identified for DTG, even in cell culture selection experiments conducted over more than 4 years (Wainberg and Han 2015). It is generally believed that the higher genetic barrier of DTG to resistance of HIV-1 is due to its slow dissociation rate from integrase-DNA complexes, in comparison with RAL and EVG (Hightower et al 2011;Geretti et al 2012;Osman et al 2015;Wainberg and Han 2015). Some studies have shown that DTG has an extended linker that allows its difluorophenyl group to enter farther into the pocket within the integrase active site, compared with other INSTIs, and that DTG has the ability to adjust its structure and conformation in response to structural changes within the active sites of RAL-and EVG-resistant integrases, compared with RAL and EVG ( Fig.…”
Section: >100 Nd <50mentioning
confidence: 99%
“…An in vitro study demonstrated that the highest genetic barrier of DTG may be attributed to its significantly slower rate of dissociation from the integrase enzyme in viruses that are either wildtype or contain the N155, Q148 or Y143 mutations [Hightower et al 2011]. Furthermore, DTG may undergo slight conformational change at the active site to overcome the physical barrier created by these single point mutations [Hare et al 2011].…”
Section: Insti Resistance Patternmentioning
confidence: 99%